Fresh Properties and Compressive Strength of 3D Printing Concrete Containing GGBS with Varies in Water-Cement Ratio - Teh Hao Wern, Calvin; Ali, Noorwirdawati (Recent Trends in Civil Engineering and Built Environment, 2024)
3D printing is an advanced construction technology that utilizes the concept of replication material layer by layer through the nozzle head. Cement is one of the materials to produce 3D printing concrete. However, it requires concrete material to fulfill the requirement of fresh and hardened properties. The major issue that arises from this innovative technique lies in the preparation and optimization of concrete materials which possess favorable printable properties that are compatible with the 3D printer in printing. This present study evaluated the fresh properties and compressive strength of 3D printing concrete. Moreover, an optimum w/c ratio of 3D printing concrete containing 30% GGBS as partial cement replacement was determined. A series of tests such as flowability test, extrudability test, buildability test, and compressive strength test was conducted. There are 30 cube specimens under 0.4-0.6 w/c ratios were tested to obtain the compressive strength of the concrete. The flowability analysis revealed that the mixture with w/c ratio 0.5 achieved a flowability value of 204mm. In terms of extrudability, the mixture S0.50 exhibited the most satisfactory results as the printing layer achieved shape retention and extruded smoothly. The buildability of the mixture S0.50 was performed better with only 0.5mm deformation and the printed layer exhibited fewer voids and was smooth. The compressive strength of mixture S0.50 increased by 39% after 28 days of curing age. As a result, the optimum w/c ratio 0.5 was determined for the 3D printing mixture.